The Versatility of Perforator-Based Propeller Flap for Reconstruction of Distal Leg and Ankle Defects - Karki, Durga (Hindawi Publishing Corporation, 2012)
Introduction. Soft tissue coverage of distal leg and ankle region represents a challenge and such defect usually requires a free flap. However, this may lead to considerable donor site morbidity, is time consuming, and needs facility of microsurgery. With the introduction of perforator flap, management of small- and medium-size defects of distal leg and ankle region is convenient, less time consuming, and with minimal donor site morbidity. When local perforator flap is designed as propeller and rotated to 180 degree, donor site is closed primarily and increases reach of flap, thus increasing versatility. Material and Methods. From June 2008 to May 2011, 20 patients were treated with perforator-based propeller flap for distal leg and ankle defects. Flap was based on single perforator of posterior tibial and peroneal artery rotated to 180 degrees. Defect size was from 4 cm × 3.5 cm to 7 cm × 5 cm. Results. One patient developed partial flap necrosis, which was managed with skin grafting. Two patients developed venous congestion, which subsided spontaneously without complications. Small wound dehiscence was present in one patient. Donor site was closed primarily in all patients. Rest of the flaps survived well with good aesthetic results. Conclusion. The perforator-based propeller flap for distal leg and ankle defects is a good option. This flap design is safe and reliable in achieving goals of reconstruction. The technique is convenient, less time consuming, and with minimal donor site morbidity. It provides aesthetically good result.